PEMANFAATAN APLIKASI GOOGLE FORM DALAM EVALUASI PEMBELAJARAN AL-QUR’AN HADIS DI MTS SHOLIHIN TANJUNG MORAWA - Nanang Pradipta; Muhammad Khairi Amri; Herbay Syahrial; Asmardi; Raisya Afifah Zahra; Luthfiah Khairani Nasution; Indra Yani Rahayu (Jurnal Pendidikan Islam, 2025)
This research explores how effectively Google Forms can be used as an evaluation tool in the Al-Qur'an Hadith subject at MTs Sholihin Tanjung Morawa. A mixed-methods approach with a sequential explanatory design was applied. Quantitative data were obtained from 40 students via questionnaires, while qualitative insights were gathered through interviews with two teachers. Findings show that students had an average score of 79.6, and 80% met the learning mastery criteria. Most students described Google Forms as easy to navigate and helpful in identifying mistakes promptly. Teachers noted that the digital format encouraged them to engage more deeply with information technology, streamlining the evaluation process. Beyond practicality, Google Forms offered students a more engaging experience, suited to the needs of today's digital environment. The study concludes that digital evaluation tools can enhance learning outcomes and digital literacy, particularly within Islamic education. It recommends providing regular training for teachers and improving school infrastructure to support wider digital adoption.